A case series of eight scoliosis patients undergone pedicle screw placement with freehand technique: study for safety and accuracy (Faculty of Medicine Universitas Indonesia, 2020)
BACKGROUND Pedicle screws and rods are routinely inserted in the vertebrae thoracic to lumbar in scoliosis reconstruction surgery to gain deformity correction and fusion. Intraoperative imaging is often needed to ensure accuracy, but surgical time will be longer and there will be more radiation exposure. Meanwhile, freehand technique is accepted as safe. This study was aimed to evaluate the accuracy of screw insertion in the freehand technique used in adolescent scoliosis surgery. METHODS This case series evaluated a total of 127 pedicle screws inserted using the freehand technique in 8 out of 28 adolescent scoliosis patients from 2011 to 2016 whom agreed for computed tomography (CT) scan follow-up from 2011 to 2016 in Dr. Seotomo Hospital, Surabaya. The accuracy and safety of the freehand technique were evaluated postoperatively in each patient using a CT scan. A successful screw was considered accurate if it was within the vertebral body and inside the safety zone (within the limit of 2–4 mm to the medial or lateral side of the vertebral body. RESULTS Of the 127 screws inserted, 106 (83.5%) were accurately placed, and 110 (86.6%) were within the safe zone. According to the level of the spine, in the upper and middle thoracic spine, the inserted screws were accurate in 69.4% and 74.9% within the safety zone, whereas in the lower thoracic and lumbar spine, 94.0% and 95.0% within the safety zone. CONCLUSIONS The freehand technique in scoliosis reconstructive surgery performed by experienced surgeons is accurate and safe.